PENGEMBANGAN MEDIA PEMBELAJARAN TALKING STICK CANDY DALAM MENINGKATKAN HASIL BELAJAR KELAS IV SD - Citra Sekar Putri Juana; Galuh Kartika Dewi; Ery Rahmawati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Learning outcomes are identifiable and measurable changes in an individual's behavior related to their knowledge, attitudes, and abilities in relation to classroom learning activities. Although students were divided into groups, researchers found that certain aspects of the students made them feel less involved in the classroom learning process. The purpose of this study was to use Talking Stick Candy learning materials to improve learning outcomes. Talking Stick Candy is an appropriate medium for IPAS learning because it is interactive and packaged in the form of a game. The research and development (R&D) technique developed by Borg and Gall was modified by the author. A total of 20 fourth-grade students from SDN Watukosek participated in this study. The material validation scored 91% (very good), and the media validation questionnaire scored 84% (very good). With the initial pre- test score falling into the good category at 44% and the post-test score rising to 80.9% in the very good category, student learning outcomes showed improvement. With a positive response rate of 88.83 (strongly agree), it can be concluded that fourth-grade students at SDN Watukosek responded positively to the use of the Talking Stick Candy media, which has proven successful in improving learning outcomes.